No One Knows for Whom He is Finally Working! The Indirect Role Played by the Rockefeller Foundation in the Shift form Poor Law Medical Relief to the National Health Service, through the London School of Hygiene and Tropical Medicine (1913-1948) (2005)
This paper seeks to analyse the transition process from the Poor Law medical relief system to the creation of the National Health Service in Great Britain and this shift’s influence on public’s health. It focuses on the analysis of the mutual relationships between British and North-American public health during the first half of the twentieth century and stresses the indirect role played by the Rockefeller Foundation in that process. The paper concentrates, on one hand, on three important junctures in the history of these relationships: the role of the Rockefeller Foundation in the creation of the London School of Hygiene in 1923, its amalgamation with the old London School of Tropical Medicine, and the subsequent emergence of the London School of Hygiene and Tropical Medicine in 1924. On the other hand, the paper analyses the impact these three events had on the birth of the British National Health Service, emphasising the role some of the London School of Hygiene and Tropical Medicine’s teachers and graduates played in designing, organising, and launching of the National Health Service. Many other scholars have written about the history of the London School of Hygiene and Tropical Medicine and about the history of the British National Health Service.2 The goal of this paper is to build upon, not to replace, what other scholars have done. However, it also aims to rescue and outline the role played by individuals in this historical process.